Taxonomy of design strategies for a circular design tool - Moreno Beguerisse, Maria; Ponte, O.; Charnley, Fiona (IOS Press, 2017)
This paper presents the development of a circular design tool created from a taxonomy of design strategies related to circular economy aspects that emerged from an extensive literature review. The taxonomy was presented to 10 experts on circular economy and design through a survey to identify an importance factor that could guide product designers to rate different concepts. The taxonomy and their rates are presented in a circular design tool to help product designers to avoid uncertainty of which design concepts meets circular economy aspects. A pair of trainers are used as an example on how the circular design tool can be used. The paper discusses how the chosen design meets the identified circular design aspects and acknowledges that more trials with different product categories are needed to determine further areas of improvement. A larger survey is also suggested to develop a more accurate scoring system when it comes to rate each concept. The paper concludes that more detail guidelines are needed for product designers in their early career, so they can consider design for circular economy. In addition, the final remarks elucidate that future research is needed to cross-reference the circular design aspects with technical aspects of each product, new manufacturing technologies and materials.